Analisis Pelaksanaan Kurikulum Merdeka di Sekolah Penggerak PAUDIT Kota Wali Demak - Fatekhah, Khoiril; Sumarno, Sumarno; Dwijayanti, Ida (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This study aims to analyze the implementation of Merdeka Curriculum in the PAUDIT Kota Wali. The research method used is qualitative with a case study approach in the PAUDIT Kota Wali. Data were collected through in-depth interviews with school principals, and questionnaires for teachers, as well as direct observation and document analysis related to curriculum implementation. The results showed that since 2022 it has started to implement the independent curriculum and become a driving school. The first implementation of the independent curriculum at PAUDIT Kota Wali is to hold a meeting with the curriculum development team and teachers to organize the KOSP. Second, download and use the guidelines provided by the Ministry of Education and Culture. Third, getting guidance support from the driving school facilitator and supervisor in implementing the Merdeka Curriculum through PMO activities. Developing the potential of students can be done through contextual learning activities, and project-based learning. The leadership ability of a school principal also influences the teachers in the school in increasing creativity, innovation, seriousness, and perseverance in organizing the implementation of the independent curriculum.